Climate Change, Gender and Resilience Issues Emerging from the 2021 United Nations Food Systems Summit: Experience from a Nigeria Case Study - Anugwa, Ifeoma Quinette (2021)
Ifeoma Quinette Anugwa SEMINAR Developing Resilience to Climate Change and Achieving Food Security in West Africa: Follow up Action from the UN Food Systems Summit Co-Organized by West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) and IFPRI SEP 30, 2021 - 09:00 AM TO 10:30 AM EDT